Proceedings of the 15th International Conference on Soft Computing and Pattern Recognition (SoCPaR 2023) Volume 3: Information Retrieval and Applications - Bajaj, Anu; Abraham, Ajith; Mishra, Pooja Manghirmalani; Ma, Kun (Lecture Notes in Networks and Systems, 2025)
XVIII, 531 p. 292 illus., 185 illus. in color.